Competition for the ANC: Dominant party losing youth and poorer sections of South African population - Melanie Müller (Stiftung Wissenschaft und Politik (SWP), 2017)
South Africa's governing party, the African National Congress (ANC), will elect a new president in December 2017. This person will also stand for the office of President of South Africa at the beginning of 2019 when President Jacob Zuma reaches the maximum number of two consecutive terms allowed by the country's constitution. It is currently unclear whether he can finish his final term. Since the dismissal of finance minister, Pravin Gordhan, resistance against Zuma has reached a new climax. A broad alliance of civil society groups, trade unions and party representatives, even some from within his own party, have called for his resignation. Although these protests are aimed directly at Zuma, the causes of the dissatisfaction lie deeper. The ANC has not been able to successfully address the country's social challenges. In addition, corruption and mismanagement have shaken confidence. For a long time, the former liberation movement was considered the only party to vote for by the black population. In the past four years, however, the ANC has faced serious competition from the Economic Freedom Fighters (EFF). Given the loss of meaning of the ANC, the South African party system is changing.
Keywords: 320